ANALISIS KURIKULUM MERDEKA: KONSEP, DASAR HUKUM, KEBIJAKAN, KARAKTERISTIK, PRINSIP PEMBELAJARAN, SERTA KELEBIHAN DAN KEKURANGAN DALAM KONTEKS PENDIDIKAN DASAR DAN MADRASAH IBTIDAIYAH - Amrina Anas; Merheliza Syirly (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study aims to examine in depth the Independent Curriculum (Kurikulum Merdeka) in the context of elementary education, particularly in primary schools and madrasah ibtidaiyah, through a literature review approach. The Independent Curriculum represents a new educational paradigm in Indonesia that emphasizes flexibility, student-centered learning, and the development of the Pancasila Student Profile. The research analyzes the basic concept of the Independent Curriculum, its legal foundation, the four main policy pillars, the holistic characteristics of learning, and the applied learning principles. Additionally, the advantages and disadvantages of this curriculum are discussed based on its implementation at the elementary level. The literature review method is employed by analyzing various recent sources addressing the urgency, implications, challenges, and innovations in the implementation of the Independent Curriculum. The analysis results indicate that the Independent Curriculum provides greater autonomy to educational units to adapt learning to local and individual student needs, particularly through differentiation approaches and projects to strengthen the Pancasila student profile. In madrasah ibtidaiyah, this curriculum successfully integrates religious values with general learning, thereby supporting the formation of religious and responsible character. Although it offers advantages such as reduced administrative burden and improved learning quality, the curriculum also faces challenges, including teacher readiness and issues in specific subjects. This study is expected to support the achievement of cognitive, affective, and psychomotor competencies among students in understanding and applying the Independent Curriculum responsibly and positively.Keywords: Independent Curriculum, differentiated learning, madrasah ibtidaiyah, Pancasila Student Profile, curriculum implementation